Association between ranolazine therapy and cognitive decline in elderly patients with ischemic heart disease - Severini, Giandomenico; Armentaro, Giuseppe; Cassano, Velia; Condoleo, Valentino; Pastura, Carlo Alberto; Panza, Alberto; Fuoco, Carlo; Miceli, Sofia; Fiorentino, Vanessa Teresa; Perticone, Maria; Maio, Raffaele; Succurro, Elena; et al. (Frontiers in Pharmacology, 2025)
IntroductionIschemic Heart Disease (IHD) represents one of the major causes of mortality and morbidity in the geriatric population This clinical complexity of these patients substantially impacts their quality of life and is associated with an increased risk of cognitive impairment (CoI). Ranolazine, plays a pivotal role in managing anginal symptoms and improving exercise tolerance.ObjectiveTo investigate the potential protective effect of Ranolazine on CoI over time in elderly patients with IHD and multiple comorbidities.MethodsWe performed a single-center, prospective, observational cohort study. The primary endpoint was a reduction in MMSE score ≥3 points during follow-up compared to baseline values.Results519 patients with a mean age of 74.2 ± 6.8 years were enrolled and divided into two groups based on Ranolazine use. The groups demonstrated comparable distribution by sex; however, Ranolazine group, although younger, displayed increased severity of anginal symptoms (Canadian Angina Scale 2.6 vs. 2.3; p < 0.0001), higher prevalence of previous acute coronary syndrome (p < 0.046), sarcopenia (p < 0.0001), and type 2 diabetes mellitus (p < 0.040). During a 4-year follow-up, 186 cases of CoI were observed (8.9 events/100 patient-years) in the general population. The incidence of CoI was significantly lower in the Ranolazine group compared to the control group (5.7 vs. 10.3 events/100 patient-years; p < 0.001). Multivariate analysis revealed a statistically significant association between CoI and the use of Ranolazine, GLP-1RAs, and SGLT2i. Specifically, Ranolazine use was associated with a 61% odds reduction in CoI.ConclusionThe use of Ranolazine is associated with a significant odds reduction in CoI in elderly patients with IHD and multiple comorbidities. The neuroprotective effect of Ranolazine may be attributed to the improvement of anginal symptoms and consequent optimization of functional status and quality of life, advocating for a comprehensive therapeutic strategy in geriatric patient management.